An Open-Source Data Storage and Visualization Back End for Experimental Data. (April 2014) - Nielsen, Kenneth; Andersen, Thomas; Jensen, Robert; Nielsen, Jane H.; Chorkendorff, Ib
In this article, a flexible free and open-source software system for data logging and presentation will be described. The system is highly modular and adaptable and can be used in any laboratory in which continuous and/or ad hoc measurements require centralized storage. A presentation component for the data back end has furthermore been written that enables live visualization of data on any device capable of displaying Web pages. The system consists of three parts: data-logging clients, a data server, and a data presentation Web site. The logging of data from independent clients leads to high resilience to equipment failure, whereas the central storage of data dramatically eases backup and data exchange. The visualization front end allows direct monitoring of acquired data to see live progress of long-duration experiments. This enables the user to alter experimental conditions based on these data and to interfere with the experiment if needed. The data stored consist both of specific measurements and of continuously logged system parameters. The latter is crucial to a variety of automation and surveillance features, and three cases of such features are described: monitoring system health, getting status of long-duration experiments, and implementation of instant alarms in the event of failure.